Integrating emerging areas of nursing science into PhD programs. - Henly, Susan J.; McCarthy, Donna O.; Wyman, Jean F.; Stone, Patricia W.; Redeker, Nancy S.; McCarthy, Ann Marie; Alt-White, Anna C.; Dunbar-Jacob, Jacqueline; Titler, Marita G.; Moore, Shirley M.; Heitkemper, Margaret M.; Conley, Yvette P. (Nursing Outlook)
The Council for the Advancement of Nursing Science aims to “facilitate and recognize life-long nursing science career development” as an important part of its mission. In light of fast-paced advances in science and technology that are inspiring new questions and methods of investigation in the health sciences, the Council for the Advancement of Nursing Science convened the Idea Festival for Nursing Science Education and appointed the Idea Festival Advisory Committee to stimulate dialogue about linking PhD education with a renewed vision for preparation of the next generation of nursing scientists. Building on the 2010 American Association of Colleges of Nursing Position Statement “The Research-Focused Doctoral Program in Nursing: Pathways to Excellence,” Idea Festival Advisory Committee members focused on emerging areas of science and technology that impact the ability of research-focused doctoral programs to prepare graduates for competitive and sustained programs of nursing research using scientific advances in emerging areas of science and technology. The purpose of this article is to describe the educational and scientific contexts for the Idea Festival, which will serve as the foundation for recommendations for incorporating emerging areas of science and technology into research-focused doctoral programs in nursing.